Faculty Senate, Strategic Plan 2011-2016: Goals and Strategies and Crosswalk - Faculty Senate, Valdosta State University (Valdosta, Ga: Valdosta State University Archives and Special Collections, 2010)
Valdosta State University. Faculty Senate, Strategic Plan 2011-2016: Goals and Strategies, November 21, 2010. Finalized May 2011. Valdosta State University. Faculty Senate, Crosswalk of Strategic Plan Goals and Strategies with Subcommittee Objectives, 2011-12 - 2015-16.
2 electronic document. Strategic Plan 2011-2016: Goals and Strategies. 3 pages. Crosswalk of Strategic Plan Goals and Strategies with Subcommittee Objectives, 2011-12 - 2015-16. 11 pages.
Keywords: Valdosta State University. Faculty Senate; Minutes (Records); Corporation reports; Committees; Electronic records